The HEARTS partner forum—supporting implementation of HEARTS to treat and control hypertension - Khan, Taskeen; Moran, Andrew E.; Perel, Pablo; Whelton, Paul K.; Brainin, Michael; Feigin, Valery; Kostova, Deliana; Richter, Patricia; Ordunez, Pedro; Hennis, Anselm; Lackland, Daniel T.; Slama, Slim; et al. (Frontiers in Public Health, 2023)
Cardiovascular diseases (CVD), principally ischemic heart disease (IHD) and stroke, are the leading causes of death (18.6 million deaths annually) and disability (393 million disability-adjusted life-years lost annually), worldwide. High blood pressure is the most important preventable risk factor for CVD and deaths, worldwide (10.8 million deaths annually).In 2016, the World Health Organization (WHO) and the United States Centers for Disease Control (CDC) launched the Global Hearts initiative to support governments in their quest to prevent and control CVD.